POLA KONSUMSI PANGAN POKOK MASYARAKAT SUKU ASEINARA DI DISTRIK BURUWAY KABUPATEN KAIMANA - Agatha Wahyu Widati; Christin Budiarti Kamakaula; Palit, Maria (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
Rice consumption that has begun to be common in the community has caused a change in people's consumption patterns for local staple foods. This study aims to determine the consumption pattern of staple foods of the Aseinara tribal people in Yarona Village, Buruway District, Kaimana Regency. The research method used is a descriptive method. The respondents in this study are the Aisenara Tribe community totaling 30 people. The results of the study show that the Aseinara people consume local staple foods in the form of sago, bananas, yams and cassava, while the non-local staple foods consumed are rice and instant noodles. The largest amount of local staple food consumption is bananas around 400 grams/day. The second highest consumption is sago around 243.3 grams/day. When compared to the local staple food consumed, the amount of non-local staple food rice has a fairly high amount of consumption, which is 1,000 grams/day